Equitable household decision making and resilience: Learning from the BRIGE Program - Anderson, Audrey (2018)
Audrey Anderson POLICY SEMINAR Addressing gender and social barriers to resilience: Measuring and leveraging household decision making for resilience Co-Organized by IFPRI and Mercy Corps JUN 27, 2018 - 09:30 AM TO 11:00 AM EDT